Road Detection in Traffic Analysis: A Context-aware Approach - Santos, Marcelo Mendonça dos (2017)
Submitted by Marcio Filho (marcio.kleber@ufba.br) on 2017-06-06T13:37:20Z No. of bitstreams: 1 dissertacao_marcelo_mendonca.pdf: 29068279 bytes, checksum: 80fb8fb6ea4e3852373e2a42c4467ea6 (MD5)